KEKUATAN HUKUM SERTIFIKAT HAK MILIK ATAS TANAH YANG DIBUAT BERDASARKAN PUTUSAN PENGADILAN - TAIRA, AGUNG SATRYA WIBAWA (Kerta Dyatmika, 2016)
ABSTRACTÂ The question of land in human life has a very close relationship at all. It is certainly understandable, because most of the life is dependent rather than soil. For that the government in order to tackle imbalances and injustices land system today, issued a regulation in the field of land law called chess orderly land covering tertip pertanaham legal, orderly administration of land use and orderly maintenance of the environment.Court decisions that have legal effect can still be used on the application certificate of land ownership, in lieu of Pejabat Pembuat Akta Tanah (PPAT) as proof of transfer of ownership of a plot of land, the whole truth of the court's decision can not be proved should be by those who feel aggrieved.